Attitude toward nudity and advertising in general through the mediation of offensiveness and moderation of cultural values: Evidence from Pakistan and the United States - Afia Khalid; Raheel Amir Awan; Faisal Qadeer; Zara Saeed; Rizwan Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
Considering the ever-increasing trend of utilizing nudity content in marketing, this study investigates whether consumers' nudity attitudes modify their attitudes toward advertising in general (AAG) and also tests the mediation of offensiveness in this path. In addition, the study also tests the boundary condition of two cultural values (conservation and openness to change) on the relationship between nudity attitude and offensiveness. A cross-sectional, online survey was used to collect primary data from consumers of Pakistan and the USA (n=311). The analysis through SPSS and PROCESS techniques confirm that offensiveness mediates the relationship between nudity attitudes and AAG. The moderating roles of conservation and openness are also supported. Cultural sensitivity towards nudity has a profound impact on advertising effectiveness and thereby successful advertisements based on nudity in one culture may fail to deliver in another because consumers develop negative AAG. The results suggest that no matter how global the brand may be, a standardized global advertising approach may not work. Therefore, advertisers should not use nudity appeals that may offend consumers in some regions and must consider cultural values when creating advertisements.
Keywords: 330; Nudity attitude; attitude towards advertising in general; advertising offensiveness; conservation value; openness to change